Prevalence of hypertension and its risk factors among transport workers in South India - Dhamodharan, S.; Megala, M.; Duraimurugan, M.; Chellavel Ganapathi, K. (International Journal Of Community Medicine And Public Health, 2020)
Background: Cardiovascular disease accounts for approximately 17 million deaths a year and complications of hypertension accounts for 9.4 million deaths worldwide every year. High blood pressure is a major public health problem in India and its prevalence is rapidly increasing. Cardiovascular disease including hypertension was most common among transport workers. Bus drivers have higher rates of mortality, morbidity and absence due to illness when compared to employees from a wide range of other occupational groups. Methods: This cross sectional study was done in south India, during June to December 2018. A total of 450 participants were selected. A self-administered questionnaire was used to collect data and summarized using descriptive statistics. A p value of <0.05 was considered significant. Results: Out of the total 450 participants, 125 (27.8%) were hypertensives. Among the hypertensives, 98 (78.4%) participants were smokers, 103 participants (82.4%) had consumed alcohol which was significantly associated with the outcome of hypertension. Lack of physical activity 108 (86.4%), excess salt 108 (86.4%) and fat intake 89 (79.2%) had statistically significant association with hypertension. A higher body mass index and waist to hip ratio more than WHO recommended range was also found to be prone to hypertension. Conclusions: The study revealed higher prevalence of hypertension was found among the drivers group compared to conductors and desk workers. Regular periodic examinations with alleviation of the above lifestyle and occupational risk factors among the three groups with special attention to drivers would help achieve apt ergonomics.